Medicine in ancient Assur a microhistorical study of the Neo-Assyrian healer Kiṣir-Aššur - Arbøll, Troels P. (Leiden Boston Brill, 2021)
"In Medicine in Ancient Assur Troels Pank Arbøll offers a microhistorical study of a single exorcist named Kiṣir-Aššur who practiced medical and magical healing in the ancient city of Assur (modern northern Iraq) in the 7th century BCE. The book provides the first detailed analysis of a healer's education and practice in ancient Mesopotamia based on at least 73 texts assigned to specific stages of his career. By drawing on a microhistorical framework, the study aims at significantly improving our understanding of the functional aspects of texts in their specialist environment. Furthermore, the work situates Kiṣir-Aššur as one of the earliest healers in world history for whom we have such details pertaining to his career originating from his own time"
Includes bibliographical references and index
Keywords: Medicine, Assyro-Babylonian; Medicine, Ancient; History, Ancient; Medicine, Arabic; Mesopotamia